An Assessment of the Effects of Micron-Particle Aggregation on the Performance of Zinc-Silica Composite Coatings Using Betti Numbers - Jianxin Xu; Xiuli Sang; Hua Wang; Yunying Fan (Advances in Materials Science and Engineering)
This paper investigates the assessment of the mixing effect of zinc-silica composite electrolyte using particle image velocimetry (PIV). In particular, we considered the deposition of silica particles using a stirring tank, which provides strong evidence for characterizing the mixing effects of flow field. A method to extract meaningful parameters to evaluate particle distribution from digital images recorded by the PIV technique during the electrodeposition process is applied. The Betti numbers of binary images of silica particles mixing were calculated using the CHomP software, which was used to evaluate mixing homogeneity and nonhomogeneity in flow field. An analysis of the performance of zinc-silica composite coatings is performed in an attempt to test and verify the assessment of the effects of micron-particle aggregation. Good correlations between calculated and experimental testing results illustrate the potential of the Betti numbers method to quantitatively evaluate micron-particle aggregation. This offers new possibilities to monitor the deposition of silica particles and to analyze flow field during the electrodeposition progress.